Nivel de autoestima y calidad de autocuidado del paciente con tratamiento de hemodiálisis en Trujillo - Cabrera Sosoya, Mayra Alejandra (2014)
Study, quantitative descriptive correlational and cross-section, which was carried out to determine the relationship between self-esteem and quality of patient self-care hemodialysis International Kidney Clinic, 2012. The theoretical approach was based on concepts of Mezzano Chronic Kidney Disease (2005), according to Daugirdas Hemodialysis (2003), Self-Esteem Orduna (2003), Armand V. Feigenbaum sorted (1963) and The Self-Care Deficit Theory of Dorothea Orem cited Marriner (2011). The population consisted of 90 patients, with a representative sample of 32 patients; instruments used to collect data were: Scale Cirilo Toro Vargas, modified by the author to measure the level of self-esteem and the questionnaire for the assessment of the quality of self-care, developed by the author. For the analysis of the test data was applied chi square statistical independence criteria (X2) in the SPPS version 16 program. Results were that 84% of patients have high self-esteem, and 16% low self-esteem; 66% of patients have good quality self-care and 34% have poor quality of self-care. In finding that there is significant relationship between the two variables (P <0.05).